Sarcoptic Mange in A Caprine: A Case Report - Sahu, Shivani; Maurya, P. S.; Jaiswal, Vikas; Kumar, Rajat; Pal, Ayush (International Journal of Livestock Research, 2024)
The goat is regarded as a poor man’s cow. It is an asset to marginal or small-scale farmers. The health of goats is adversely affected by parasites. A two and half-year-old, ram was presented to the IFFCO camp with a complaint of itching, alopecia, and dry lesions in the inner and outer aspect of hind quarters. The skin-scrapping examination revealed the presence of Sarcoptes scabiei. The goat was successfully treated with ivermectin at the dose of 0.2 mg/kg body weight, S/C along with the external application of Taktic (Amitraz) @ 4 ml/litre dilution. Timely diagnosis and prompt treatment are essential for the maintenance of productivity in an animal.